Effect of the Rare Earth Element Lanthanum (La) on the Growth and Development of Citrus Rootstock Seedlings - Hang Yin; Junxiu Wang; Yao Zeng; Xinjian Shen; Yizhong He; Lili Ling; Li Cao; Xingzheng Fu; Liangzhi Peng; Changpin Chun (Plants, 2021)
Rare earth elements (REEs) can affect the growth and development of plants. However, few studies have been carried out on the effects of REEs on citrus seedlings. In this study, the growth parameters, toxicity symptoms, chlorophyll content, and La content of three citrus rootstocks are analyzed under different concentrations of La, a representative REE. The results show that the growth of citrus rootstock seedlings was stimulated at La ≤ 0.5 mmol·L−1 and inhibited at concentrations above 1 mmol·L−1. The chlorophyll and carotenoid contents of trifoliate orange (Poncirus trifoliata L. Raf.) and Ziyang Xiangcheng (C. junos Sieb. ex Tanaka) leaves of plants grown at low concentrations of La (≤1.5 mmol·L−1) were similar to those of the control but were significantly reduced at 4 mmol·L−1 La. Toxic symptoms gradually appeared with increasing La concentrations, with yellowed leaves and burst veins appearing at 4 mmol·L−1 La. The symptoms of toxicity were most severe in trifoliate orange, followed by Shatian Pomelo (Citrus grandis var. shatinyu Hort) and then Ziyang Xiangcheng. Moreover, in leaves, the Ca content was significantly negatively correlated with La content (p < 0.01). These results indicate that La has a hormesis effect on the growth of citrus rootstocks. Of the studied citrus seedlings, Ziyang Xiangcheng is the most resistant to La.